The empirical success of Keynesianism - Donald Gillies (Economic Thought, 2020)
The main thesis of this paper is that the empirical success of Keynesianism shows it to be scientific. Keynesianism here refers not to a specific theory, but to a paradigm. It is argued that Kuhn's notion of paradigm can be applied to economics, but, in contrast to the natural sciences, in economics there are always competing paradigms. The principal ones in contemporary economics are the Neoclassical, Keynesian and Marxist. To investigate whether the Keynesian paradigm is scientific we need a criterion for the scientificity of a paradigm. The paper first considers one approach to this problem due to Kant, but this is rejected as incorrect and called 'the Kantian fallacy'. Another approach is then put forward: 'the empirical confirmation principle', and reasons are given for accepting this as correct. Using this principle, it is thThe main thesis of this paper is that the empirical success of Keynesianism shows it to be scientific. Keynesianism here refers not to a specific theory, but to a paradigm. It is argued that Kuhn's notion of paradigm can be applied to economics, but, in contrast to the natural sciences, in economics there are always competing paradigms. The principal ones in contemporary economics are the Neoclassical, Keynesian and Marxist. To investigate whether the Keynesian paradigm is scientific we need a criterion for the scientificity of a paradigm. The paper first considers one approach to this problem due to Kant, but this is rejected as incorrect and called 'the Kantian fallacy'. Another approach is then put forward: 'the empirical confirmation principle', and reasons are given for accepting this as correct. Using this principle, it is then argued that that Keynesianism is indeed scientificen argued that that Keynesianism is indeed scientific.
Keywords: 330; confirmation; Kantian fallacy; Keynes; Kuhn; paradigm; Neoclassical economics